Bioassay for Hamycin and Amphotericin B in Serum and Other Biological Fluids - Shadomy, Smith (1969)
A bioassay suitable for measuring concentrations of the polyene antifungal agents hamycin and amphotericin B in biological fluids is described. By using Paecilomyces varioti as the indicator organism, sensitivity of the bioassay was found to be in the range of 0.01 to 0.02 μg/ml. A linear dose-response curve was obtained with amphotericin B; the curve for hamycin was curvilinear. In a series of assays, hamycin serum levels in the range of 0.01 to 3.5 μg/ml were measured; with amphotericin B, serum levels in the range of 0.015 to 0.175 μg/ml were measured in patients receiving orthodox intravenous medication and as high as 9.0 μg/ml in one patient treated with extraordinarily high doses of the drug.